Correlation between subjective perception and objective parameters for the characterisation of fibre print-through on surfaces of class A carbon fibre reinforced plastics via multidimensional scaling. (December 2018) - Kraemer, Matthias; Dauser, Thomas; Middendorf, Peter; Bauernhansl, Thomas
Abstract: Fibre print-through on the surfaces of composites emerges as a consequence of the heterogeneous mix of matrix and reinforcing fibres and is one of the obvious surface imperfections that differentiates them from conventional materials. Visible surfaces in the body shell of vehicles demand high Class A requirements without any surface imperfections. Currently, fibre print-through on glossy painted surfaces is evaluated subjectively by human auditors. An overreliance on subjective human evaluation has arisen due to a lack of methods and parameters for characterising this phenomenon. To understand which characteristics are responsible for human perception and to determine suitable parameters for the evaluation of print-through effects, the subjective perception of 25 participants measured by multidimensional scaling is correlated to a fitted parameter regarding fibre print-through and conventional parameters such as long- or shortwave, or the arithmetic mean R a . The comparison of various characteristics of fibre print-through to coated aluminium enables a limiting value to be set based on perception.